Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
0,5.x-2/3.x=5/12
(0,5-2/3).x =5/12
(-1/6).x =5/12
x =5/12:(-1/6)
x =-5/2
Vậy x=-5/2
Pt \(\Leftrightarrow\dfrac{1}{2}x-\dfrac{2}{3}x=\dfrac{5}{12}\)
\(\Leftrightarrow x\left(\dfrac{1}{2}-\dfrac{2}{3}\right)=\dfrac{5}{12}\)
\(\Leftrightarrow-\dfrac{1}{6}.x=\dfrac{5}{12}\)
\(\Leftrightarrow x=-\dfrac{5}{2}\)
0,5.x-\(\dfrac{2}{3}\).x=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)\(\dfrac{1}{2}\).x-\(\dfrac{2}{3}\).x=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x.(\(\dfrac{1}{2}\)-\(\dfrac{2}{3}\))=\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x.\(\dfrac{-1}{6}\) =\(\dfrac{5}{12}\)
\(\Leftrightarrow\)x =\(\dfrac{5}{12}\):\(\dfrac{-1}{6}\)
\(\Leftrightarrow\)x =\(\dfrac{5}{12}\).\(\dfrac{-6}{1}\)
\(\Leftrightarrow\)x = \(\dfrac{-5}{2}\)
\(0,5x-\frac{2}{3}x=\frac{5}{2}\)
\(\Rightarrow\frac{1}{2}x-\frac{2}{3}x=\frac{5}{2}\)
\(\Rightarrow x\left(\frac{1}{2}-\frac{2}{3}\right)=\frac{5}{2}\)
\(\Rightarrow x\frac{-1}{6}=\frac{5}{2}\)
\(\Rightarrow x=\frac{5}{2}:\frac{-1}{6}=-15\)
\(\text{a)}25\%-\frac{3}{2}+0,5.\frac{12}{5}\)
\(=\frac{1}{4}-\frac{3}{2}+\frac{1}{2}.\frac{12}{5}\)
\(=-\frac{5}{8}+\frac{6}{5}\)
\(=-\frac{25}{40}+\frac{48}{40}\)
\(=\frac{23}{40}\)
\(b)0,25.\frac{7}{3}.30.\text{ }0,5.\frac{8}{45}\)
\(=\frac{1}{4}.\frac{7}{3}.30.\frac{1}{2}.\frac{8}{45}\)
\(=\frac{7}{12}.(30.\frac{8}{90})\)
\(=\frac{7}{12}.\frac{8}{3}\)
\(=\frac{14}{9}\)
\(c)\frac{9}{23}.\frac{5}{8}+\frac{9}{23}.\frac{3}{8}-\frac{9}{23}\)
\(=\frac{9}{23}.\left(\frac{5}{8}+\frac{3}{8}-1\right)\)
\(=\frac{9}{23}.0\)
\(=0\)
1/2x - 2/3x = 7/12
(1/2 - 2/3)x = 7/12
1/10x = 7/12
x = 7/12 : 1/10
x = 35/6
a) \(\dfrac{1}{4}+\dfrac{\dfrac{3}{4}}{3x}=-5\)
\(\dfrac{\dfrac{3}{4}}{3x}=-5-\dfrac{1}{4}\)
\(\dfrac{\dfrac{3}{4}}{3x}=-\dfrac{21}{4}\)
\(3x=\dfrac{\dfrac{3}{4}}{-\dfrac{21}{4}}\)
\(3x=-\dfrac{1}{7}\)
\(x=\dfrac{-\dfrac{1}{7}}{3}\)
\(x=-\dfrac{1}{21}\)
a) 1/4 + 3/4 : 3x = -5
3/4 : 3x = -5 - 1/4
3/4 : 3x = -21/4
3x = 3/4: -21/4
3x = 1/-7
x = 1/-7 : 3
x = 1/-21
b) x - 25%x = 0,5
1.x - 1/4 . x = 1/2
(1 - 1/4) . x = 1/2
3/4 . x = 1/2
x = 1/2 : 3/4
x = 1/2 . 4/3
x = 2/3